2002
DOI: 10.1017/s0959259802012261
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic agents in frail elderly patients

Abstract: Use of the term frailty in the medical literature has increased significantly in the last 20 years. A MEDLINE search using the combined terms ‘frail’ and ‘elderly’ yielded 473 articles published between 1996 and 2001, compared with 85 between 1980 and 1985. This increasing interest in frailty has been fuelled by evidence that the ‘frail elderly’ are the group most likely to benefit from geriatric intervention programmes and by the close links between frailty and longer hospital stays, nursing home utilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 103 publications
(120 reference statements)
0
1
0
Order By: Relevance
“…Reduced muscle mass and strength are phenomena seen in GH deficiency, in disuse, and in aging, 9–12 but GH replacement in older people has had incomplete success because strength effects have been inconstant, and there have been concerns about the effect of GH on other factors, such as glucose homeostasis 11–13 . A randomized, placebo‐controlled trial of human GH (hGH) in 111 older adults (aged 60) with hip fractures demonstrated a similarly equivocal result 14 .…”
mentioning
confidence: 99%
“…Reduced muscle mass and strength are phenomena seen in GH deficiency, in disuse, and in aging, 9–12 but GH replacement in older people has had incomplete success because strength effects have been inconstant, and there have been concerns about the effect of GH on other factors, such as glucose homeostasis 11–13 . A randomized, placebo‐controlled trial of human GH (hGH) in 111 older adults (aged 60) with hip fractures demonstrated a similarly equivocal result 14 .…”
mentioning
confidence: 99%